Burden and psychological symptoms on informal caregivers of the elderly in the COVID-19 pandemic - Giuliana Duarte de Oliveira da Silva; Gabriela Martins; Luana Aparecida da Rocha; Mariane Teixeira Machado; Henrique Pott Junior; Aline Cristina Martins Gratão (Revista Gaúcha de Enfermagem, 2022)
ABSTRACT Objective To evaluate the burden and psychological symptoms of informal caregivers of the elderly during the COVID-19 pandemic. Method Cross-sectional study with 50 caregivers from the Gerontology Outpatient Clinic in the interior of São Paulo, evaluated in 2021 via teleconsultation by the Hospital Anxiety and Depression Scale and the Zarit-Brief Burden Interview. Poisson’s multivariate regression was applied to the two instruments scores according to the set of characteristics of the participants. Results Psychological symptoms were highlighted in caregivers with longer time in exercise (p=0.01; p=0.001) and who lived in the same environment with the elderly (p=0.04; p=0.02). Burden was associated with age (p<0.001) and living with the elderly (p=0.001). Conclusion There is a need for interventions that attenuate psychological symptoms and burden in older caregivers, who live with the elderly and have been working for a longer time.